Exploring the knowledge system in building information modeling (BIM) technology for medical construction projects (MCPS): A bibliometric analysis and prospective direction - Jiahao Chen; Laemthong Laokhongthavorn (Ain Shams Engineering Journal, 2024)
This paper investigates the knowledge system in Building Information Modeling (BIM) technology in Medical Construction Projects (MCPs). Specifically, it proposes knowledge graph analysis utilizing scient metric techniques and employs VOSviewer and CiteSpace software to analyze the consequence of relevant statistics from the literature concerning BIM medical construction projects (BIM-MCPs). In order to analyze the collaboration network, the analysis of the co-occurrence network, and the analysis of the co-citation network, 83 journal articles were gathered. The results obtained from the research indicate that (a) the intellectual framework of BIM-MCPs can be categorized into four distinct clusters. (b) The research focus in BIM-MCPs has evolved, including model development, frameworks, implementation, system integration, application throughout the entire lifecycle, emergency medical engineering project applications, and intelligent management of medical facilities and smart buildings. (c) Prospective directions for research are delineated in three distinct areas: enhancement of use for BIM Medical Facility Management (BIM-MFM), integration of BIM technology in sustainability assessment, and application of BIM technology in emergency medical engineering and smart medical construction.
Keywords: BIM and Construction Integration; Construction Project Management and Performance; Occupational Health and Safety Research